TPST2-mediated receptor tyrosine sulfation enhances leukocidin cytotoxicity and S. aureus infection - He, Jie; Yang, Xianggui; Yang, Kai; Xu, Honglin; Chen, Cheng; Wang, Junxiong; Zeng, Jun (Frontiers in Immunology, 2023)
Background An essential fact underlying the severity of Staphylococcus aureus (S. aureus) infection is the bicomponent leukocidins released by the pathogen to target and lyse host phagocytes through specific binding cell membrane receptors. However, little is known about the impact of post-transcriptional modification of receptors on the leukocidin binding. Method In this study, we used small interfering RNA library (Horizon/Dharmacon) to screen potential genes that affect leukocidin binding on receptors. The cell permeability was investigated through flow cytometry measuring the internalization of 4′,6-diamidino-2-phenylindole. Expression of C5a anaphylatoxin chemotactic receptor 1 (C5aR1), sulfated C5aR1 in, and binding of 6x-His–tagged Hemolysin C (HlgC) and Panton-Valentine leukocidin (PVL) slow-component to THP-1 cell lines was detected and analyzed via flow cytometry. Bacterial burden and Survival analysis experiment was conducted in WT and myeloid TPST-cko C57BL/6N mice. Results After short hairpin RNA (shRNA) knockdown of TPST2 gene in THP-1, HL-60, and RAW264.7, the cytotoxicity of HlgAB, HlgCB, and Panton–Valentine leukocidin on THP-1 or HL-60 cells was decreased significantly, and the cytotoxicity of HlgAB on RAW264.7 cells was also decreased significantly. Knockdown of TPST2 did not affect the C5aR1 expression but downregulated cell surface C5aR1 tyrosine sulfation on THP-1. In addition, we found that the binding of HlgC and LukS-PV on cell surface receptor C5aR1 was impaired in C5aR1+TPST2− and C5aR1−TPST2− cells. Phagocyte knockout of TPST2 protects mice from S. aureus infection and improves the survival of mice infected with S. aureus. Conclusion These results indicate that phagocyte TPST2 mediates the bicomponent leukocidin cytotoxicity by promoting cell membrane receptor sulfation modification that facilitates its binding to leukocidin S component.